2004
DOI: 10.1523/jneurosci.1628-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor Homologous Factor 2B: Association with Nav1.6 and Selective Colocalization at Nodes of Ranvier of Dorsal Root Axons

Abstract: Voltage-gated sodium channels interact with cytosolic proteins that regulate channel trafficking and/or modulate the biophysical properties of the channels. Na v 1.6 is heavily expressed at the nodes of Ranvier along adult CNS and PNS axons and along unmyelinated fibers in the PNS. In an initial yeast two-hybrid screen using the C terminus of Na v 1.6 as a bait, we identified FHF2B, a member of the FGF homologous factor (FHF) subfamily, as an interacting partner of Na v 1.6. Members of the FHF subfamily share … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
174
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(189 citation statements)
references
References 50 publications
12
174
3
Order By: Relevance
“…2) and our observations that FGF13 can affect other ion channels, such as voltage-gated Ca 2+ channels in cardiac myocytes (34). Another possibility is that the FGF13 within the AIS is in transition to developing nodes of Ranvier, because FGF13 has been found concentrated in nodes of Ranvier in dorsal root ganglion neurons (43). Nevertheless, the different roles for FGF13 and FGF14 in hippocampal neurons are consistent with the importance of cellular context in determining the actions of any specific FHF (44), a phenomenon that is also highlighted by the opposing effects of FGF13 in hippocampal neurons compared with the heart.…”
Section: Discussionmentioning
confidence: 64%
“…2) and our observations that FGF13 can affect other ion channels, such as voltage-gated Ca 2+ channels in cardiac myocytes (34). Another possibility is that the FGF13 within the AIS is in transition to developing nodes of Ranvier, because FGF13 has been found concentrated in nodes of Ranvier in dorsal root ganglion neurons (43). Nevertheless, the different roles for FGF13 and FGF14 in hippocampal neurons are consistent with the importance of cellular context in determining the actions of any specific FHF (44), a phenomenon that is also highlighted by the opposing effects of FGF13 in hippocampal neurons compared with the heart.…”
Section: Discussionmentioning
confidence: 64%
“…This effect was not observed in similar studies on Nav1.6. By contrast, ectopic expression FHF2b increased the maximal activatable whole cell Nav1.6 sodium currents by 2-fold (Wittmack et al, 2004). This may be attributable to either increased surface channel density or to more efficient activation of available surface channels.…”
Section: Fhf Binding Proteins: II Vgscsmentioning
confidence: 87%
“…Since then, it has been shown that FHFs can bind to Nav1.5, which is expressed in cardiac myocytes (Liu et al, 2003), and to Nav1.6, the principal channel mediating initiation and propagation of action potentials in most mature neurons of the central and peripheral nervous systems (Shtraizent and Goldfarb, 2005;Wittmack et al, 2004). Native complexes of FHFs with sodium channels have been detected by coimmunoprecipitation from extracts of brain or dorsal root ganglia (M. Goldfarb, unpublished data).…”
Section: Fhf Binding Proteins: II Vgscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this diversity has clearly complicated the field, FGFs' role as Na v channel interacting proteins has been solidified by the discovery of a highly conserved Na v interaction site within the FGF core domain that interacts with specific amino acids within the Na v C termini (2). FGF14 and Na v channels are enriched at the axon initial segment (AIS) of several neuronal types, whereas FGF13 colocalizes with Na v 1.6 at nodes of Ranvier of dorsal roots of primary afferents (5). Of note is that nodal localization was seen using a pan FGF13 antibody, but an antibody that is specific to FGF13S (also known as FGF13A or FHF2A) did not immunolabel nodes of Ranvier, showing important isoform and splice variant differences (6).…”
mentioning
confidence: 99%